#TITLE_ALTERNATIVE# - Dharmayanti Hutabarat (NIM : 15113098), Dewi
<palign="justify">One of the methods which was studied in region mapping acceleration for being land registration basemap is small format aerial photogrammetry using DJI Phantom 4. In this research, data acquisition was conducted in Talang Jawa Village, Ogan Komering Ulu district, South Sumatera Province which included coordinate data and photos data. There are 14 points of GCPs coordinate, 4 points of ICPs coordinate, and 894 photos covering the whole area Talang Jawa Village. Things to know in accuracy product are lens specification and calibration, GCP measurement accuracy, GCP tagging on photos. Lens of FC330_3.6 camera in Phantom 4 needs calibration. Processing photos into orthomosaic used Pix4D software which has three self calibration methods that are Standard, Alternative and Accurate geolocation and Orientation methods. There are two types of internal parameters optimalization, ALL type (all internal parameters are optimized) and Leading type (some internal parameters are optimized : f, K1, K2). This research is also determined three GCP configuration those are 5 GCP configuration, 10 GCP configuration and 14 GCP configuration. Based on the configuration, calibration methods,and calibration type being analyzed, the most optimal GCP accuracy as required is Accurate Geolocation and Orientation methods in ALL type with 10 GCP configuration, Standard methods in ALL type with 10 GCP configuration,and Standard methods in Leading type with GCP 10 configuration. These third processing can generate 1 : 2500 scale map based on Accuracy standard from ASPRS and 1 : 2500 in second class, 1: 5000 in first class based on regulation of geospatial information agency number 15 of 2014 . Regulation of The Minister of Agrarian Affairs / Head of The National Land Agency Number 3 of 1997 concerning on Implementation of Government Regulation Number 24 of 1997 on Land Registration at provision 13 verse 1 which stated that the required land registration basemap is 1 : 1000 Ã‚Â– 1 : 2500 map scale. Based the regulation, this orthomosaic can be used as basemap of land registration as an acceleration of mapping region.<palign="justify">